Pelestarian Sistem Pengelolaan Adat di Desa Panglipuran Yang Berkelanjutan Kepada Generasi Muda - Wanudyastuti, Arini; Maulidah, Izza; Athaya, M. Rakha; Al Ferina, Faniya; Tri Setiyoko, Didik (Cahaya Smart Nusantara, 2025)
The aim of this research is to see how the traditional traditional management system of Penglipuran Village can be maintained and passed on to the next generation. This research collects data about the role of local wisdom in maintaining social harmony and the village environment using a qualitative descriptive approach. The research results show that traditional principles encourage people to maintain cleanliness and environmental sustainability. The Tri Hita Karana concept is the main foundation of social life which emphasizes a balanced relationship between humans, God, fellow humans and nature. The main strategy for preserving cultural heritage is local wisdom practices, such as managing sacred places, environmental conservation, and the tradition of mutual cooperation. Tourism development in Penglipuran Village prioritizes the preservation of cultural and environmental values ​​as well as economic growth. Therefore, Penglipuran Village is a real example of how the younger generation can inherit a sustainable traditional management system to maintain cultural identity and preserve the environment.